Overview of the findings - Khairul Anuar, A.; Nooriah, M.S.; Farizah, M.H.; Merina, P. (Faculty of Medicine, University of Malaya, 2002)
The findings of this project have given us an insight of the health status and some of the health problems of the foreign workers currently employed in Malaysia.